Nutritional screening in a cancer prehabilitation programme: A cohort study. Issue 2 (4th August 2022) - Burden, Sorrel T.; Bibby, Neil; Donald, Kirsty; Owen, Kellie; Rowlinson‐Groves, Kirsty; French, Chloe; Gillespie, Loraine; Murphy, Jack; Hurst, Sarah Jayne; Mentha, Robert; Baguley, Karly; Rowlands, Ash; et al.
Abstract: Background: Cancer patients are often malnourished pre‐operatively. The present study aimed to establish whether current screening was appropriate for use in prehabilitation and investigate any association between nutritional risk, functionality and quality of life (QoL). Methods: This cohort study used routinely collected data from September 2020 to August 2021 from patients in a Prehab4cancer programme. Included patients were aged ≥ 18 years, had colorectal, lung or oesophago‐gastric cancer and were scheduled for surgery. Nutritional assessment included Patient‐Generated Subjective Global Assessment (PG‐SGA) Short‐Form and QoL with a sit‐to‐stand test. Association between nutritional risk and outcomes was analysed using adjusted logistic regression. Results: From 928 patients referred to Prehab4Cancer service over 12 months, data on nutritional risk were collected from 526 patients. Pre‐operatively, 233 out of 526 (44%) patients were at nutritional risk (score ≥ 2). During prehabilitation, 31% of patients improved their PG‐SGA and 74% of patients maintained or improved their weight. Odds ratios (OR) with confidence intervals (CI) showed that patients with better QoL using EuroQol‐5 Dimensions (OR = 0.05, 95% CI = 0.01, 0.45, p  = 0.01), EuroQol Visual Analogue Scale (OR = 0.96, 95% CI = 0.93, 1.00, p  = 0.04) or sit‐to‐stand (OR = 0.96, 95% 0.93, 1.00, p = 0.04) were less likely to be nutritional at risk. Conclusions: Almost half of patients in Prehab4Cancer programme assessed using PG‐SGA were at risk of malnutrition. However, almost half of the sample did not have their risk assessed. Patients at risk of malnutrition were more likely to have a poorer QoL and sit‐to‐stand test than those who were not at risk. Key points: Colorectal, lung or oesopho‐gastric cancer patients referred to the Prehab4Cancer service underwent a nutritional assessment. Almost half of patients assessed using the Patient‐Generated Subjective Global Assessment (i.e., PG‐SGA) were at risk of malnutrition. Patients at risk of malnutrition were more likely to have a worse quality of life and sit‐to‐stand test indicating reduced physical function than those who were not at risk of malnutrition. This indicates that optimising the nutritional status of cancer patients in the prehabilitation period can maximise the nutritional status, functionality and quality of life of patients.